Improvements of Population Fitness and Trophic Status of a Benthic Predatory Fish Following a Trawling Ban - Tao, Lily S. R.; Mak, Yanny K. Y.; Ho, Valerie C. M.; Sham, Ronia C.-t.; Hui, Tommy T. Y.; Lau, Danny C. P.; Leung, Kenneth M. Y. (Frontiers in Marine Science, 2021)
Trawl fisheries have been shown to cause overfishing and destruction of benthic habitats in the seabed. To mitigate these impacts, a trawling ban has been enforced in Hong Kong waters since 31st December 2012 to rehabilitate the ecosystem and enhance fisheries resources. Previous studies demonstrated that reduced trawling activities would increase the heterogeneity of benthic habitats, thereby enhancing species richness and abundance of benthic fauna and providing more prey resources for predatory fishes. This study aimed to test a hypothesis that the population and trophic dynamics of the Bartail flathead Platycephalus indicus, a heavily fished benthic predatory fish, at inner and outer Tolo Channel of Hong Kong (i.e., EI and EO) improved with increases in their body size, abundance, biomass, trophic niche and trophic position after the trawl ban. Samples were collected from trawl surveys before and after the trawl ban to compare the pre- and post-ban populations of P. indicus from EI and EO. Body size, abundance and biomass were assessed in 2004, 2013–2014 and 2015–2016, while trophic niche and trophic position were analysed based on stable isotopes of fish samples collected in dry season of 2012, 2015 and 2018. Following the trawl ban, the abundance and biomass of P. indicus increased in EO, with body size increased in EI. Furthermore, as indicated by the results of stable isotope analysis on their tissues and prey items, trophic niche and trophic position of P. indicus increased in EI and EO, respectively. Our study demonstrated that the trawl ban had promoted the recovery of a predatory fish population through restoring size structure and trophic dynamics.